“Gerobak Online”: A Model of Community Economic Empowerment During the Covid 19 Pandemic Based on a Mosque via the Zakat Collection Unit of the Al Fatah Mosque in Pacul Village, Bojonegoro Regency - Eko Arief Cahyono; Lisa Aminatul Mukaromah; Agil Mutiara Nurjanah; Yulia Indahsari; Khurul Anam (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2023)
Zakat Collection Unit (UPZ) Masjid is one of the institutions assisting Baznas in optimizing zakat administration and distributing zakat to mustahiq in line with zakat beneficiaries' asnaf. In accordance with the applicable legislation, UPZ mosques are granted the authority and responsibility as a unit or extension of the district Baznas in helping the administration of zakat, infaq, and alms, as well as their usage to promote the welfare of the people, particularly the congregation. mosque from underprivileged households. This research employs a qualitative methodology, which provides a thorough, precise, and in-depth account of events, people's actions, or locations. This study employs a qualitative methodology to provide a comprehensive explanation of Online Cart: A Model for Developing the Economic Potential of the People in a Pandemic Period Based on the Zakat Collection Unit (UPZ) at the Al Fatah Mosque in Pacul Village, Bojonegoro Regency. Researchers employed ethnographic approaches to determine the economic issues facing the community, particularly those experienced by the mosque congregation. This research was undertaken at the Al Fatah Mosque in Pacul Village, Bojonegoro District, since its administration is deemed competent of handling zakat and bolstering the mosque congregation's finances.. This study demonstrates the effectiveness of zakat management in empowering and enhancing the economy of mosque congregations through the Zakat Collecting Unit (UPZ) in the Online Cart program, as proven by the operation of mustahiq small enterprises owned by empowered individuals. Where about five individuals are empowered in this program and have their own superior items. In this initiative, UPZ Masjid Al Fatah Pacul receives help and supervision in the form of training in digital marketing, packaging, and production of new goods, as well as partnering with Baznas Bojonegoro and the Bojonegoro Department of Industry and Manpower to build mustahiq capabilities.